Indonesian Government Bond Stochastic Simulation - Koesrindartoto, Deddy P; Adventius, Fernando (SBM ITB, 2011)
This paper proposes a government bond portfolio stochastic simulation using a Vasicek Model, a generally used model of term structure of interest rates. The model is used to generate the possible term structure of interest rates for five years based on the historical term structure. The future government debts are forecasted using ARIMA model, and the efficient frontier of costs resulting from portfolios of bond with different maturity structures are determined from the Cost-at-Risk framework. An optimization process will be conducted on the government bond portfolio efficient frontier based on the government risk preference.Keywords: Yield Curve, Vasicek Model, ARIMA, Cost-at-Risk, financing strategy, maturity